A toolkit for women: the mis(sed) management of gender in resource industries. Issue 6 (11th July 2016) - Laplonge, Dean
Abstract : Purpose: – The purpose of this paper is to show the extent to which work on how to manage gender in resource industries fails to draw on the body of knowledge which explores gender in the workplace. Design/methodology/approach: – This paper explores the efficacy of a recently published toolkit within the context of the current debate about gender in resource industries (such as mining, and oil and gas). Findings: – The Australian Human Rights Commission's toolkit speaks to this debate, but fails to analyse existing strategies to deal with the "gender problem"; it simply repeats them as successful examples of what to do. The authors of the toolkit also fail to ask a question which is fundamental to the success of any intervention into gender: what is the definition of "gender" on which the work is based? Originality/value: – The debate about gender in resource industries fails to take into consideration contemporary ideas about gender as they have appeared in academic research and human practice.